Formulasi dan Uji Efek Lilin Aromaterapi Minyak Atsiri Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) terhadap Immobility time Mencit (Mus musculus) Jantan yang Dibuat Stres: Aromatherapy Assay of Scented candles of Aromatic Pandan Leaf (Pandanus amaryllifolius Roxb.) Essential Oil against Stressed Male Mice (Mus musculus) - Chikita Inaku; Muhammad Yusuf; Sinar Praktisi (LPPM Universitas Abdurrab, 2023)
Fragrant Pandan is a plant that has been used in traditional medicine, this leaf contains linalool compounds which are efficacious as a sedative so that it can increase a sense of comfort, and suppress aggression and anxiety. This study aimed to determine the physical stability of the aromatherapy wax formula of fragrant pandan leaf essential oil (Pandanus amaryllifolius Roxb.) and its antistress effect on male mice (Mus musculus). The design of this study was a post-test only control group design, using 25 male mice divided into 5 groups, each group consisting of 5 animals exposed to the aromatherapy wax formula of pandan leaves essential oil for 1 hour with various concentratioins of essential oils, where the group I have given 1%, group II was given 2%, group III was given 3%, group IV was given negative control, and group V was given positive control. The results of the research on the physical stability test of the aroma therapy wax formula of pandan fragrant leaf essential oil showed that the formula was organoleptically stable with white color and characteristic odor, the melting point test was stable at temperatures of FI 54O, FII 53OC, and FIII 52OC, time test FI burning shows 4 hours 28 minutes, FII 2 hours 52 minutes and FIII 3 hours 34 minutes, the preference test before and aftrer burning shows the higher the concentration of essential oils the panelists prefer. The results of the antistress effect test showed that the immobility time of mice at KI at 291 seconds, KII at 182 seconds, KIII at 88 seconds, and KIV as a negative control was higher at 334 seconds, which means that at concentrations of 1%, 2%, 3% had an antistress effect with sig analysis values Post-Hoc Tukey Statistics FIII 1,00, F IV 0,00, and FV 1,00